Associations of serum leptin, ghrelin and peptide YY levels with physical activity and cardiorespiratory fitness in adolescent boys with different BMI values - Liina Remmel; Vallo Tillmann; Priit Purge; Evelin Lätt; Jaak Jürimäe (Termedia Publishing House, 2017)
The aim of this study was to investigate the differences in associations of serum acylated and des-acylated ghrelin, peptide YY (PYY) and leptin levels with physical activity (PA) and cardiorespiratory fitness (CReF) in adolescent boys (mean age of 14.0 years) with overweight (OWB; n=55) and with normal weight (NWB; n=154). Methods: Total PA was measured by 7-day accelerometry (counts/min) and CReF by peak oxygen consumption (VO2peak/kg). Results: No differences were found in serum PYY, acylated ghrelin or des‑acyl ghrelin levels, whereas mean leptin (11.6±10.6 vs. 2.0±2.7 ng/ml; p<0.05) and insulin (18.1±8.7 vs. 11.0±6.2 mU/l; p<0.05) levels were significantly higher in OWB compared to NWB. Mean CReF was significantly lower in OWB compared to NWB (39.7±8.7 vs. 50.5±6.8 ml/min/kg; p<0.05). Leptin was negatively correlated with CReF in both groups (r=-0.43; p<0.05), des-acylated ghrelin with CReF only in OWB (r =-0.36; p<0.05). In OWB leptin was negatively correlated with total PA (r=-0.32; p<0.05) and positively with sedentary time of PA (r=0.35; p<0.05). In NWB 28.1% of the variability of CReF was determined by leptin and insulin resistance index (HOMA-IR), whereas in OWB 71.9% was determined by trunk FM and BMI. Conclusions: Leptin concentration was inversely associated with CReF in adolescent boys independently of BMI in both groups, while des-acylated ghrelin was associated with CReF only in OWB. Low PA in OWB was associated with high serum leptin level.